What ecological prediction for Cola nitida: an indigenous fruit species in Benin? - Noudossessi Rufin, Kpatinnon; Nounagnon Gérard, Gouwakinnou; Akoeugnigan Idelphonse, Sode; Alex Franck Rodrigue, Idohou; Imorou Ismaïla, Toko; Glele Romain Lucas , Kakaï; Jean Cossi, Ganglo (Revue Ecosystèmes et Paysages, 2023)
The variation of climatic parameters influences the distribution of several indigenous fruit species in Benin. This research evaluates the spatio-temporal dynamics of favorable habitats to the cultivation of Cola nitida under current climatic conditions and by 2085 in Benin. To do this, 230 occurrences of C. nitida were combined with the environmental layers using the MaxEnt algorithm in order to highlight its favorable habitats. The AUC (0.969) and SEDI (0.918) results suggest a very good performance of the model. The precipitation of the driest quarter (43.6%) and the maximum temperature of warmest month (41.8%) are the variables that most influenced the geographical distribution of C. nitida in Benin. More than 87% of the national territory remains less favorable to the conservation of C. nitida. Very favorable habitats went from 5.21% (present climatic conditions) to 1.29% (RCP 4.5) i.e., a loss of 3.92%, and occupy only 0.16% of the national territory (RCP 8.5) either a regression of 5.05%. Furthermore, the priority conservation habitats resilient to climate change occupy only 9.69% of the territory. Thus, it is important to implement reforestation projects in priority natural habitats resilient to climate change (classified forest of Pahou, Ouèdo, Djigbé, Itchèdè-Toffo, Niaouli and the reforestation perimeter of Abomey) which are entirely suitable for the conservation of C. nitida. The promotion of C. nitida in agroforestry parks should be encouraged for sustainable production and management.